The role of international rogatory in combating corruption crimes - Fadul Youssef Idries (International Journal of Law Research and Studies, 2025)
This research addresses the role of international rogatory in combating corruption crimes. The research aims to define the legal system for international rogatory as the most important form of judicial cooperation at the regional and international levels. The research uses a descriptive, analytical, and comparative approach, reviewing information from various sources. The problem of this study lies in the adequacy and binding nature of international rogatory in combating corruption crimes, in light of international and regional agreements and domestic laws. It also addresses the extent to which the controls contained in these agreements constrain discretionary power in implementing rogatoryThe study recommended that international rogatory should only be used if it is the only means of achieving a fair resolution of the case. It also recommended the formation of a central authority to deal positively with requests for judicial assistance, along with the creation of a special unit to handle requests for international rogatory in corruption crimes.
Keywords: International Rogatory; Judicial Cooperation; Corruption Crimes; Judge's Authority